Beans - Yerkes Leslie (Recorded Books, Inc., 2009)
Based on the success story of a small Seattle coffee shop, this little book is a tasty brew of sound principles and instructive anecdotes. As the coffee shop owner looks for ways to retain his customer base, a consultant helps him focus on what really matters. Authors Yerkes and Decker, renowned for their consulting and business savvy, have done their homework and turned Beans into "a business fable taken from real life."